(untitled) (REVISTA DE ESTUDOS INTERDISCIPLINARES, 2025)
The objective was to evaluate the effect of educational actions on the consumption and knowledge related to the utilization of whole foods in school-age children. Also, to evaluate the physicochemical composition of the products. School-aged children (32) answered a questionnaire on consumption and knowledge about whole food utilization (Pre-Intervention). Then, they participated in theoretical-practical educational actions on the subject (Intervention), which included the preparation of food products with radish residues in cooking workshops. In the Post-Intervention, the children answered the same questionnaire as in the Pre-Intervention. The food products were evaluated in relation to the physicochemical composition. In general, the intervention improved children’s consumption and knowledge about the use of whole foods. The products with radish residue additive, prepared in the cooking workshops, presented high acceptability indices, above 80%. In addition, they were classified with a nutritional profile favorable for human consumption, especially relating to minerals and fiber. It is concluded that educational interventions are effective strategies to improve children’s learning on topics related to the whole utilization of food. Furthermore, food products made with radish residue in cooking workshops show good sensory acceptability among children, besides having a good nutritional profile.